ANALISIS PENGARUH BEBAN PAJAK, TUNNELING INCENTIVE DAN MEKANISME BONUS TERHADAP TRANSFER PRICING PADA PERUSAHAAN MULTINASIONAL YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Dini Andhika; Sparta Sparta (Ibs Press, 2024)
The purpose of this study is to determine and analyze the effect of income tax variable, tunneling incentive and bonus mechanism to transfer pricing. The sample selection using purposive sampling method and the sample of this research are 8 multinational companies listed in Indonesian Stock Exchange (IDX). The data are obtained from secondary data of annual report of basic and multinational companies listed in Indonesian Stock Exchange in 2016 to 2020. The analysis technique used is binary logistic regression analysis. The hypothesis in this study is based on previous research and various other supporting theories The results of this study indicate that the income tax and tunneling incentive have a negative effect on transfer pricing, while the Bonus Mechanism has a positive effect on transfer pricing.